Effectiveness of the Infectious Disease (COVID-19) Simulation Module Program on Nursing Students: Disaster Nursing Scenarios - Hwang, Won Ju; Lee, Jungyeon (Journal of Korean Academy of Nursing, 2021)
This study aimed to develop an emerging infectious disease (COVID-19) simulation module for nursing students and verify its effectiveness. A one-group pretest-posttest quasi-experimental study was conducted with 78 under-graduate nursing students. A simulation module was developed based on the Jeffries simulation model. It consisted of pre-simulation lectures on disaster nursing including infectious disease pandemics, practice, and debriefings with serial tests. The scenarios contained pre-hospital settings, home visits, arrival to the emergency department, and follow-up home visits for rehabilitation. Disaster preparedness showed a statistically significant improvement, as did competencies in disaster nursing. Confidence in disaster nursing increased, as did willingness to participate in disaster response. However, critical thinking did not show significant differences between time points, and neither did triage scores. The developed simulation program targeting an infectious disease disaster positively impacts disaster preparedness, disaster nursing competency, and confidence in disaster nursing, among nursing students. Further studies are required to develop a high-fidelity module for nursing students and medical personnel. Based on the current pandemic, we suggest developing more scenarios with virtual reality simulations, as disaster simulation nursing education is required now more than ever.